The influence of social norms and perceived fairness on voluntary tax compliance: The mediating role of personal norms and trust in government - Marfiana, Andri; Widyastuti, Tri; Darmansyah, Darmansyah (Educoretax, 2025)
This study aims to analyze the factors influencing voluntary tax compliance in Indonesia, with a focus on social norms, personal norms, perceived of fairness, and trust in the government. The method employed is a quantitative approach using surveys, involving the distribution of questionnaires to individual taxpayers who are not employees in the Jabodetabek area. The data were analyzed using PLS-SEM (Partial Least Squares Structural Equation Modeling) to test the relationships among the variables in the research model. The results of the study show that social norms positively influence voluntary tax compliance, both directly and through the formation of personal norms as a mediator. Furthermore, the Perceived of fairness in the tax system was found to enhance trust in the government, which in turn positively affects voluntary tax compliance. These findings provide important insights that psychological and social factors, such as social norms, fairness, and trust in the government, play a key role in enhancing voluntary tax compliance. Therefore, it is recommended that tax policies focus on improving fairness and transparency, as well as strengthening social norms that support tax compliance.